Predictive Modelling and Optimization of Power Plant Nitrogen Oxides Emission - Ilamathi P; V. Selladurai; K. Balamurugan (Institute of Advanced Engineering and Science, 2012)
A predictive modelling of nitrogen oxides emission from a 210 MW coal fired thermal power plant with combustion parameter optimization is proposed. The oxygen concentration in flue gas, coal properties, coal flow, boiler load, air distribution scheme, flue gas outlet temperature and nozzle tilt were studied. The parametric field experiment data were used to build artificial neural network (ANN). The coal combustion parameters were used as inputs and nitrogen oxides as output of the model. The predicted values of the ANN model for full load condition were verified with the actual values. The optimum level of input operating conditions for low nitrogen oxides emission was determined by simulated annealing (SA) approach. The result indicates that the combined approach could be used for reducing nitrogen oxides emission.DOI: http://dx.doi.org/10.11591/ij-ai.v1i1.286